Modelling and forecasting multivariate realized volatility - Roxana Chiriac; Valeri Voev (University of Konstanz, Center of Finance and Econometrics (CoFE), 2008)
This paper proposes a methodology for modelling time series of realized covariance matrices in order to forecast multivariate risks. The approach allows for flexible dynamic dependence patterns and guarantees positive definiteness of the resulting forecasts without imposing parameter restrictions. We provide an empirical application of the model, in which we show by means of stochastic dominance tests that the returns from an optimal portfolio based on the model's forecasts second-order dominate returns of portfolios optimized on the basis of traditional MGARCH models. This result implies that any risk-averse investor, regardless of the type of utility function, would be better-off using our model.
urn:nbn:de:bsz:352-opus-116658
Keywords: C32; C53; G11; 330; Forecasting; Fractional integration; Stochastic dominance; Portfolio optimization; Realized covariance